Children, young people and dark tourism - Kerr, Mary Margaret; Stone, Philip R.; Price, Rebecca H. (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"This book is the first its kind to offer an innovative examination of the intersecting influences, contexts, and challenges within the field of children's dark tourism. It also outlines novel conceptualizations and methods for scholarship in this overlooked field. Presently, tourism research, and in dark tourism specifically, relies primarily on adult-centered theories and data collection methods. However, these approaches are inadequate for understanding and developing children's experiences and perspectives. This book seeks to inform and inspire research on children's experiences of dark tourism. Designed to appeal to students and scholars, it brings together insights from leading experts. The book focuses on five themes, to explore the conceptual and historic origins of children's dark tourism, developmental contexts, child perspectives, specific contexts relevant to children's encounters, and methodological approaches. This book is aimed at an international array of scholars and students with inherent research interests in the contemporary commodification of death and 'difficult heritage' within the visitor economy. Thus, the book will provide a multi-disciplinary scope within the fields of history, heritage studies, childhood studies, psychology, education, sociology, human geography, and tourism studies. The volume is primarily intended for undergraduate and postgraduate study, as well as scholars and tourism professionals"--
'Seen but not heard': Children in (Dark) Tourism Research Agendas -- Young Tourists' Experiences at Dark Tourism Sites: Toward a Conceptual Framework -- The Youngest Tourists: Early Childhood Considerations and Challenges -- School-Aged Tourists: Pre-Adolescent and Adolescent Considerations and Challenges -- Development of Death Concepts: Childhood and Adolescence: Considerations for Tourist Experience and Research -- Young Tourists with Disabilities: Considerations and Challenges -- Interpretation For Children: Turning Horror and Hurt Into Healing and Hope -- Understanding Children's Visits to Difficult Heritage Sites: Children's Sense of Place -- Difficult Heritage and the Digital Child: Challenges and Opportunities -- 'Why is it so fun to be scared?' Entertainment in Dark Tourism -- 'Edutainment' in Dark Tourism: Towards a Child's Perspective -- 'Deconstructing Dark History and Difficult Heritage': Engaging High School Students in the Use of Historiographical Analysis Techniques -- School Trips: A Unique Form of Student Learning for Dark Tourism Studies -- Young People and Dark Commemorative Events: The Centenary of World War One in Australia -- Identity and Belonging in a Dark Heritage Destination: Perspectives from Local Children -- Ethical Research with Children and Young People: Addressing Complexities in (Dark) Tourism -- Research Methods for Studying Young Tourist Experiences -- Research Collaborations with Schools -- Co-Research with Youth: A Conceptual Model and Case Study.
Keywords: Dark tourism; Youth -- Travel; Children and death; Children and violence; Children and war; BUSINESS & ECONOMICS -- Industries -- Hospitality, Travel & Tourism